Effect of Balanced Fertilization in Puddled Rice on the Productivity of Lentil in Rice-Fallow System Under Zero Tillage (Bangladesh Agronomy Journal, 2016)
Lentil (Lens culinaris Medik) predominantly grows under rainfed conditions under residual soil moisture in most of the rice-fallows in India with low productivity. Imbalanced NPK (N1), recommended dose of NPK (N2) and recommended NPK + 10 t ha-1 FYM (N3) were applied in kharif rice (var. IET 4786) through consecutive three years (2011-2013). Two lentil varieties viz. Asha (B-77) and Subrata (WBL-58) were sown after rice under zero tillage conditions keeping standing residues and mulch through utilizing residual moisture and nutrients. Zero tillage with straw mulch (ZT-M) in both lentil varieties conserved 12-20% more water than residue removal (ZT) and 7-10% more than standing residue (ZT-H), respectively. During flowering (60 DAS) surface soil (0-5 cm) of ZT attained 0.8 MPa as compared to 0.2 and 0.1 MPa for ZT-H and ZT-M, respectively. Soils with N3 stored more water and depleted lesser than N2 and N1 which produced higher biomass, leaf relative water content (RWC) and chlorophyll content. Soil thermal variation in ZT-M tends to proliferate root and nutrient uptake that increased 19 and 14% more yield and 25 and 15% more water use efficiency (WUE) than ZT-H and ZT. Both Subrata and Asha performed well under zero tillage conditions. Zero tillage and nutrient management had an effect on soil microbial biomass carbon (SMBC) and dehydrogenase activity as ZT < ZT-H < ZT-M and N3 > N2 > N1. Proper technology with application of zero tillage may explore the possibility of growing lentil crops in rice fallows during postrainy season utilizing carry-over soil moisture and residual soil fertility.Bangladesh Agron. J. 2016, 19(1): 67-79